TOMOGRAPHY IMAGING OF THE SOURCE AREA OF THE 2018 LOMBOK EARTHQUAKES SEQUENCE USING LOCAL SEISMOGRAPH NETWORK - Afif, Haunan
The series of strong earthquakes that occurred in Lombok Island on 29 July (M 6.4), 5 August (M 7.0), 9 August (M 5.9), and 19 August (M 6.3 and M 6.9) 2018 caused significant damages, economic loses, and victims. Study about the structure and characteristics of earthquake source zones are strongly important to find out how strong earthquakes are generated. Seismic tomography is one of proper method for describing subsurface seismic velocity structures and widely used in and around strong earthquake source zones. We determined three-dimensional (3D) seismic velocity structures around the source region of 2018 Lombok-Indonesia earthquakes by employing local earthquake tomography. The data consist of 28,728 P- and 20,713 S-wave arrival times from 3,259 events which were recorded by 20 local seismic stations. The results show that most of the significant earthquakes (M 7.0 on 5 August 2018, M 5.9 on 9 August 2018, and M 6.3 on 19 August 2018) occurred in a massive fault zone with high Vp and high Vs anomalies, and moderate to high Vp/Vs ratio. Whereas a low velocity area with high Vp/Vs ratio value appears in the middle of fault zone that indicates the presence of fluid content. The aseismic zone appears in the northwest of Rinjani Volcano dominated by crustal fluids characterized by low velocities, and moderate to high Vp/Vs ratio zone. A massive mass such as dry rock was imaged to the east of Rinjani Volcano characterized by high Vp and high Vs, and lower Vp/Vs, which is supported by a high Bouguer anomaly. The existence of the Sumbawa Strait Strike-Slip Fault is depicted by the presence of low Vp, low Vs, and high Vp/Vs beneath the fault line.